1992
DOI: 10.1007/bf01741144
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the antigenic phenotype of human breast carcinoma cells by modifiers of protein kinase C activity and recombinant human interferons

Abstract: In the present study we have analyzed the effect of a synthetic protein kinase C (PKC) activator 3-(N-acetylamino)-5-(N-decyl-N-methylamino)-benzyl alcohol (ADMB) and the natural PKC-activating tumor-promoting agents 12-O-tetradecanoylphorbol 13-acetate (TPA) and mezerein on the antigenic phenotype of T47D human breast carcinoma cells. All three agents increased the surface expression of the tumor-associated antigen BCA 225 and various cellular antigens, including HLA class II antigens, intercellular adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…6). Some earlier evidence also has suggested that the antigenic phenotypes of breast carcinoma and astrocytoma cells can be modified by IFN-␤ treatments (51,52), and dramatic antitumor activity has been noted in a patient with ovarian cancer treated with immunotherapy and adenovirally expressed IFN-␤ (53). The diverse nature of such cellular IFN-␤ responses suggested that the up-regulatory process was either dependent on normal ubiquitous factors, or factors aberrantly expressed in each of these tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…6). Some earlier evidence also has suggested that the antigenic phenotypes of breast carcinoma and astrocytoma cells can be modified by IFN-␤ treatments (51,52), and dramatic antitumor activity has been noted in a patient with ovarian cancer treated with immunotherapy and adenovirally expressed IFN-␤ (53). The diverse nature of such cellular IFN-␤ responses suggested that the up-regulatory process was either dependent on normal ubiquitous factors, or factors aberrantly expressed in each of these tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by such findings and with the intent to identify simplified PE analogs using a function-oriented synthesis (FOS) strategy [19][20][21] , we reported in 1986 a computerbased analysis of the pharmacophore of PEs and related PKC modulating ligands, which led to the first designed PKC modulator-3-(N-acetylamino)-5-(N-decyl-N-methylamino)-benzyl alcohol (ADMB) 22 . In 1992, Leon et al 23 showed that ADMB, like the PEs, enhanced tumor associated antigen (BCA-225) expression in breast carcinoma cells but, unlike PEs, it did not induce shedding of the antigen, highlighting the potential for natural product-inspired designed analogs to exhibit divergent and superior biological activity. Significantly, the immunomodulatory properties of the PEs are not unique to this structural class of PKC modulators.…”
mentioning
confidence: 99%
“…An LS174T and SW480 (colorectal), HeLa (cervical), DU-145 (prostate), and HONE-1 (nasopharyngeal) (9,(22)(23)(24)(25), were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum (DMEM-10) at 37°C in a 5% C02/95% airhumidified incubator. Additional human cell types including HBL-100 (normal mammary epithelial), HO-1 and C8161 (melanoma), GBM-18 and T98G (glioblastoma multiforme), and Saos-2 (human osteosarcoma) were maintained under similar conditions.…”
mentioning
confidence: 99%